Integration of One-Pair Spatiotemporal Fusion With Moment Decomposition for Better Stability - Ma, Yaobin; Wei, Jingbo; Huang, Xiangtao (Frontiers in Environmental Science, 2021)
Spatiotemporal fusion has got enough attention and many algorithms have been proposed, but the practical stability has not been emphasized yet. Observing that the strategies harnessed by different types of algorithms may lead to various tendency, an integration strategy is introduced to make full use of the complementarity between different types of spatiotemporal fusion algorithms for better fusion stability. In our method, the images fused by two different types of methods are decomposed into components denoting strength, structure, and mean intensity, which are combined separately involving characteristic analysis. The proposed method is compared with seven algorithms of four types by reconstructing Landsat-8, Landsat-7, and Landsat-5 images to validate the effectiveness of the spatial fusion strategy. The digital evaluation on radiometric, structural, and spectral loss illustrates that the proposed method can reach or approach the optimal performance steadily.